DOES sketchup make improve students' visual-spatial skills? - Abdullah, Abdul Halim (Institute of Electrical and Electronics Engineers Inc., 2022)
This study was conducted with two objectives: (a) to develop 3D geometry teaching strategies through SketchUp Make (SPPD-SUM), and (b) to study the effect of SPPD-SUM on visual-spatial skills (VSS). It was conducted in two stages. Stage I involved designing SPPD-SUM, whereas Stage II involved studying of the effect of SPPD-SUM on VSS. The activities in Stage I were based on a five-phase cycle in the ADDIE Model. The analysis phase examined the basic information related to VSS. The design phase involved setting VSS into learning activities. The development phase involved the construction of learning activities that are in line with every VSS component. The implementation phase involved two series of pilot studies and the implementation of SPPD-SUM among 12 students for three weeks. The data obtained from the evaluation phase by seven mathematics experts found that SPPD-SUM might function well pedagogically. Stage II began with descriptive quantitative data and inferential statistics using a one-group quasi time series experimental approach. The study was conducted for six weeks among 34 form-five students. The inferential analysis via the mean score of VSS suggests that SPPD-SUM helps improve students' VSS with a significant difference (at p = 0.05 level) before and after learning activities. This quantitative analysis shows that there is a significant change in students' cognitive processes, particularly in their ability to rotate, view, transform and mentally cut 3D objects, and to identify, analyse, connect, and make series reasoning and geometric features. Therefore, it can be concluded that SPPD-SUM can be used in mathematics classrooms to improve students' visual-spatial skills.